Mobile app for enhancing user experience in teleconsultation using metaverse - Thum, Yi Wen (Nanyang Technological University, 2023)
The rapid evolution of the metaverse and its integration with AR, VR, and AI technologies presents a groundbreaking opportunity to transform teleconsultation in the healthcare sector. This project aims to use immersive technology to create an environment conducive to effective therapeutic intervention to address mental health issues. The mobile app introduces features such as a secure authentication process for seamless user access, a comprehensive search functionality enabling patients to locate psychotherapists based on specialized expertise, and a streamlined appointment booking system facilitating convenient access to therapy sessions. The integration of a VR video player within the app empowers psychotherapists to guide patients through immersive VR experiences tailored to alleviate stress and anxiety during consultations, thereby enhancing the therapeutic outcomes.